Superselective Catheter Angiographies of the Wrist (SCAW): Approaches for Vascularized Bone Grafts - Leonie Goelz; Simon Kim; Andreas Eisenschenk; Sven Mutze; Ariane Asmus (Diagnostics, 2023)
Background: This study assesses the variability of the palmar radiocarpal artery (PRCA), dorsal carpal branch of the ulnar artery (DCBUA), and anterior interosseous artery (AIA) in superselective catheter angiographies of the wrist (SCAW). Methods: Secondary analysis of consecutive SCAW (2009–2011). Measurements of the distances of the PRCA to the midface of the radiocarpal joint, the DCBUA to the styloid process of the ulnar, and maximum diameters of PRCA, DCBUA, and AIA. Results: Seven female and ten male patients (mean 35 years) received SCAW. All patients suffered from Kienbock’s disease. The mean distance from the PRCA to the radiocarpal joint was 7.9 ± 2.3 mm and the distance from the DCBUA to the styloid process of the ulna was 29.6 ± 13.6 mm. The mean maximum diameter of the PRCA was 0.6 ± 0.2 mm, that of the DCBUA was 1.1 ± 0.4 mm, and that of the AIA 1.2 ± 0.3 mm. In six cases (35%), all three arteries contributed to the PRCA; in eight cases (47%), the radial and AIA; in two cases (12%), the radial and ulnar artery; and in one case (6%), only the radial artery contributed. Conclusions: SCAW are feasible to assist in preoperative planning. Os pisiforme transfer with DCBUA might be the best choice for a vascular bone graft in Kienbock’s disease.